2017
DOI: 10.3892/ol.2017.6038
|View full text |Cite
|
Sign up to set email alerts
|

The lipid metabolism gene FTO influences breast cancer cell energy metabolism via the PI3K/AKT signaling pathway

Abstract: The present study assessed the effect of the lipid metabolism, fat mass and the obesity-associated gene (FTO), on energy metabolism of breast cancer cells. The human breast cancer cell lines, MCF-7 and MDA-MB-231, and HCC1937 human breast cells were studied. Real-time PCR was used to measure the levels of FTO mRNA from breast cancer cells and normal breast cells. MDA-MB-231 cells were transfected with miFTO inhibitor or inhibitor control, and cells were assessed for levels of lactic acid, ATP, pyruvate kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 21 publications
1
55
1
2
Order By: Relevance
“…Indeed, the FTO gene variant related to cancer risk is unlikely independent of adiposity ( 100 ). In addition, it was reported that by targeting the PI3K/AKT signaling, FTO influences breast cancer cell energy metabolism including lactic acid, ATP, pyruvate kinase activity, and hexokinase activity ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the FTO gene variant related to cancer risk is unlikely independent of adiposity ( 100 ). In addition, it was reported that by targeting the PI3K/AKT signaling, FTO influences breast cancer cell energy metabolism including lactic acid, ATP, pyruvate kinase activity, and hexokinase activity ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt pathway is associated with characteristics of carcinogenesis and is frequently activated in numerous human cancer types, such as in non-small cell lung cancer [ 46 ], colorectal cancer [ 47 ], breast cancer [ 48 ] and prostate cancer [ 49 ]. In addition, a recent study showed that women with CC commonly display PI3K pathway alterations, indicating its potential value in the treatment of advanced and metastatic disease [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanically, in our results, the phosphorylation of PI3K and AKT was inhibited by Mn12Ac. Previous studies reported that BRD4, FTO, and MACC1 could positively regulate the phosphorylation of PI3K and AKT, and miR‐200a and miR‐200b could negatively regulate the levels of p‐PI3K and p‐AKT . Whether Mn12Ac inhibited the phosphorylation of PI3K and AKT by regulating the above genes or other downstream genes should be the subject of future studies.…”
Section: Discussionmentioning
confidence: 93%